2017
DOI: 10.1093/brain/awx272
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic editing of the Dlg4/PSD95 gene improves cognition in aged and Alzheimer’s disease mice

Abstract: The Dlg4 gene encodes for post-synaptic density protein 95 (PSD95), a major synaptic protein that clusters glutamate receptors and is critical for plasticity. PSD95 levels are diminished in ageing and neurodegenerative disorders, including Alzheimer's disease and Huntington's disease. The epigenetic mechanisms that (dys)regulate transcription of Dlg4/PSD95, or other plasticity genes, are largely unknown, limiting the development of targeted epigenome therapy. We analysed the Dlg4/PSD95 epigenetic landscape in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 75 publications
2
105
0
Order By: Relevance
“…Here we show that the aggregate of PSD-95 interactome abundance is also associated with cognitive trajectory. Bustos and colleagues showed that increased protein level of PSD95 in the hippocampus rescued memory deficits of aged mice and dementia mice 53 . Their finding is consistent with ours in which over-expression of PSD95 protein was associated with cognitive stability.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that the aggregate of PSD-95 interactome abundance is also associated with cognitive trajectory. Bustos and colleagues showed that increased protein level of PSD95 in the hippocampus rescued memory deficits of aged mice and dementia mice 53 . Their finding is consistent with ours in which over-expression of PSD95 protein was associated with cognitive stability.…”
Section: Discussionmentioning
confidence: 99%
“…[102] PSD-95 encoding gene (DLG4) is found on chromosome 17 (17p13.1), spanning approximately 30 kb, and is associated with neurological disorders as previously discussed. [105] PSD-95 has also been found to have higher expression levels in the lateral amygdala in patients with MDD, compared to healthy individuals, [106] while a recent study showed no difference in epigenetic factors in the prefrontal cortex and hippocampus. Variations in DLG4 have been associated with schizophrenia [103,104] and it was recently shown that epigenetic editing of DLG4 could rescue memory deficits in a mouse model of Alzheimer's disease.…”
Section: Targeting Pdz Domains Of Postsynaptic Density Protein 95/synmentioning
confidence: 99%
“…We assessed the long-term (24 h) spatial memory in 6-month-old C9BAC and control mice, using the object location memory (OLM) task. OLM is a simple single-trial behavioral memory task, in which rodents are allowed to explore freely (avoiding stress) and rely on the rodent's innate preference for novelty [49,50]. Animals were presented with a non-displaced (ND) versus displaced (D) object in the OLM test (Fig.…”
Section: Reduced Nuclear Staining Of H3k9me3 In Hippocampal Neurons Omentioning
confidence: 99%